Etiologia zaburzeń spektrum autyzmu – przegląd koncepcji - Szmania, Lidia (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2015)
Researches are still trying to figure out what is the real cause of autism. In the years several major concepts conceming patogenical mechanisms of this disease has not been determined. However, none of them turned out to be entirely good. The purpose of this article is to systematically review the concepts and select the ones that have been proven empirically.